Parental age is related to the occurrence of cleft lip and palate in Brazilian populations - Paulo Henrique Pimenta de Carvalho; Renato Assis Machado; Silvia Regina de Almeida Reis; Daniella Reis Barbosa Martelli; Verônica Oliveira Dias; Hercílio Martelli Júnior (Universidade Estadual de Campinas, 2017)
Aim: To evaluate the association of environmental risk factors, particularly paternal and maternal age, with gender and type of oral cleft in newborn with nonsyndromic cleft lip with or without cleft palate (NSCL/P). Methods: This study included 1,346 children with NSCL/P of two Brazilian Services for treatment of craniofacial deformities. Parental ages were classified into the following groups: maternal age <35, 36-39, and ≥40 years; paternal age <39 and ≥40 years. The data was analyzed with chi-square test and multinomial logistic regression analysis. The odds ratios were estimated with a 95% confidence interval. Results: Of the 1,346 children included in this study, CLP was the type of NSCL/P with highest prevalence, followed by, respectively, CL and CP. There was a greater occurrence of NSCL/P in males compared to females (55.8% versus 44.2%). CLP was more common in men, while the CL and CP were more prevalent in women (p=0.000). No association between maternal age and clefts was observed (p=0.747). However, there was evidence of association between father's aged ≥40 years old and NSCL/P (p=0.031). When patients with CP were analyzed separately, no association between the father's age and the child's gender (p=0.728) was observed, i.e. the female gender prevails among patients with CP, regardless of the father's age. Conclusions: This study showed that there were differences in the distribution of the non-syndromic cleft lip and/or palate and the gender, and fathers aged ≥40 years old may have increased risk of oral cleft. Further studies involving different populations are needed for a better understanding of the effect of maternal and paternal ages as a risk factor for the occurrence of oral clefts.